2021
DOI: 10.3389/fvets.2021.687079
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Spike Glycoprotein Gene of Swine Acute Diarrhea Syndrome Coronavirus Strain CH/FJWT/2018 Isolated in China

Abstract: Swine acute diarrhea syndrome (SADS) is a highly contagious infectious disease characterized by acute vomiting and watery diarrhea in neonatal piglets. The causative agent for SADS is the swine acute diarrhea syndrome coronavirus (SADS-CoV), an alphacoronavirus in the family Coronaviridae. Currently, SADS-CoV was identified only in Guangdong and Fujian provinces of China, not in any other regions or countries in the world. To explore the genetic diversity of SADS-CoV isolates, herein we comparatively analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…At the same time, some strains of SADSr‐CoV and SADS‐CoV showed topological inconsistencies in the evolutionary trees, suggesting the occurrence of recombination as well as cross‐species transmission. We also found that among the many SADS‐CoV isolates, CH/FJWT/2018 (MH615810) from Fujian in 2018 showed the closest evolutionary relationship to SADSr‐CoV, consistent with previous findings that the S gene of this virus is less similar to other SADS‐CoVs 10 . Therefore, to a certain extent, MH615810 is an unusual strain, which was also reflected in the recombination, as analyzed below.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…At the same time, some strains of SADSr‐CoV and SADS‐CoV showed topological inconsistencies in the evolutionary trees, suggesting the occurrence of recombination as well as cross‐species transmission. We also found that among the many SADS‐CoV isolates, CH/FJWT/2018 (MH615810) from Fujian in 2018 showed the closest evolutionary relationship to SADSr‐CoV, consistent with previous findings that the S gene of this virus is less similar to other SADS‐CoVs 10 . Therefore, to a certain extent, MH615810 is an unusual strain, which was also reflected in the recombination, as analyzed below.…”
Section: Discussionsupporting
confidence: 89%
“…After this, the virus was silent for some time in Guangdong, with no related reports until 2019, when the virus broke out again, in an area close to where the original outbreak occurred in 2017 9 . There were reports of reemergence in Fujian in 2018 10 . In 2021, SADS‐CoV re‐emerged in Guangxi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SADS-CoV is a highly pathogenic CoV that infects pigs and has a unique cleavage site (R-Y-V-R | I) in the S1 domain (region 1 in Figure 3) that is essential for cell fusion and may have an impact in the pathogenicity of this virus and its observed broad cell range (67). Comparative genetic analyses have shown that bat CoV HKU2 is closely related to SADS-CoV, suggesting that bat CoVs may also be involved in the emergence of pathogenic CoVs of veterinary importance (55).…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by acute diarrhea, vomiting, dehydration and high mortality in neonatal piglets, resulting in enormous economic losses (1)(2)(3). The pathogens associated with viral diarrhea disease in piglets are mainly coronaviruses, including TGEV, PEDV, PDCoV, and SADS-CoV (4)(5)(6)(7)(8)(9). These swine enteric viruses cause similar clinical symptoms in infected pigs, leading to difficulties in diagnosing diarrhea (10).…”
Section: Introductionmentioning
confidence: 99%